Reconstructing Islamic Agricultural Financing Regulations: A Socio-Legal Study using Soft Systems Methodology - Ahmad Muqorobin; Use Etica; Nunung Rodliyah; Akmal Hidayah; Mohamed Rashid Ab Razak (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
Despite its constitutional role in supporting food sovereignty, Banyuwangi’s agricultural sector remains excluded from formal Islamic finance due to a regulatory gap between rigid banking standards and agricultural risk. This study identifies a Proximity Paradox, in which Islamic banks are structurally disincentivized from financing smallholders. Using Soft Systems Methodology (SSM) as a socio legal approach and drawing on empirical data from farmers, Islamic banks, and Bayt al-Māl wa al-Tamwīl (BMTs), the research formulates an Agricultural Financing Regulatory Model. The model recommends policy reform by the Financial Services Authority (Otoritas Jasa Keuangan, OJK) and the National Sharia Council (Dewan Syariah Nasional–Majelis Ulama Indonesia, DSN-MUI), including hybrid value chain contracts, mandatory agricultural takaful, and a formal Bank–BMT linkage scheme, to align banking compliance with agricultural realities and promote distributive justice (‘adl).